Use of Protein Pegylation to Prolong the Antiviral Effect of IFN Against FMDV - Diaz-San Segundo, Fayna; Medina, Gisselle N.; Azzinaro, Paul; Gutkoska, Joseph; Mogulothu, Aishwarya; Attreed, Sarah E.; Lombardi, Kimberly R.; Shields, Jacob; Hudock, Teresa A.; de los Santos, Teresa (Frontiers in Microbiology, 2021)
Interferons (IFNs) are considered the first line of defense against viral diseases. Due to their ability to modulate immune responses, they have become an attractive therapeutic option to control virus infections. In fact, like many other viruses, foot-and-mouth disease virus (FMDV), the most contagious pathogen of cloven-hoofed animals, is highly sensitive to the action of IFNs. Previous studies demonstrated that type I, II and III IFNs, expressed using a replication defective human adenovirus 5 (Ad5) vector, can effectively block FMDV replication in vitro and can protect animals when challenged one day after Ad5-IFN treatment, in some cases providing sterile immunity. Rapidly spreading FMD is currently controlled with vaccination, although development of a protective adaptive immune response takes 5 to 7 days. Therefore, an optimal strategy to control FMD outbreaks is to block virus replication and spread through sustained IFN activity while the vaccine-stimulated adaptive immune response is developed. Challenges with methods of delivery and/or with the relative short IFN protein half-life in vivo, have halted the development of such approach to effectively control FMD in the animal host. One strategy to chemically improve drug pharmacodynamics is the use of pegylation. In this proof-of-concept study, we demonstrate that pegylated recombinant porcine (po)IFNα displays strong and long-lasting antiviral activity against FMDV in vitro and in vivo, completely protecting swine against FMD for at least 5 after a single dose. These results highlight the potential of this biotherapeutics to use in combination with vaccines to fully control FMD in the field.